FREQUENCY OF IMPAIRED GLUCOSE TOLERANCE IN DIFFERENT GRADES OF OBESITY - Khalid Amin; Amin Anjum (Journal of University Medical & Dental College, 1970)
ABSTRACT Introduction Impaired glucose tolerance (IGT) is a pre-diabetic condition. It is defined as fasting glucose less than 7.0 mmol/l (<126mg/dl) with a two hours glucose tolerance value of 7.8-11.0 mmol/l (140-199mg/dl). Impaired glucose tolerance is characterized by hyperglycemia and insulin resistance and considered to be a risk factor in development of diabetes mellitus. Objective The objective of this study is to determine the frequency of impaired glucose tolerance in different grades of obesity. Study design Cross sectional study. Setting This study was conducted in the Medical Unit-IV outpatient department (OPD), DHQ Hospital, Faisalabad. Duration with dates Six months from 1st May 2010 to 31st October 2010. Subjects and methods A total of 150 patients with body mass index >25 were selected for this study. Oral glucose tolerance was done to see the relation of impaired glucose tolerance with respect to different grades of obesity which are obese-1 if body mass index is >25 but <30 and obese-2 if ≥ 30. 75g oral glucose was given after overnight fasting and blood sample taken before and after two hours. Results: The mean age of the patients was 37.8±7.8 years. There were 47 (31.3%) male patients and 103 (68.7%) female patients. The mean height of the patients was 1.6±0.1 meters. The mean weight of the patients was 80.4±14.2 kg. The mean body mass index of the patients was 31.7±3.1 kg/m2. There were 55 (36.7%) patients of grade I obesity and 95 (63.3%) patients of grade II obesity. There were 14 (9.3%) patients who had positive impaired glucose tolerance test and 136 (91.7%) patients had negative impaired glucose tolerance test. Conclusion: It is concluded from this study that frequency of impaired glucose tolerance is common in patients with different grades of obesity occurred in 9.3% of all cases.